2021
DOI: 10.1302/2633-1462.27.bjo-2021-0029.r1
|View full text |Cite
|
Sign up to set email alerts
|

Converting hip and knee arthroplasty cases to same-day surgery due to COVID-19

Abstract: Aims In 2020, the COVID-19 pandemic meant that proceeding with elective surgery was restricted to minimize exposure on wards. In order to maintain throughput of elective cases, our hospital (St Michaels Hospital, Toronto, Canada) was forced to convert as many cases as possible to same-day procedures rather than overnight admission. In this retrospective analysis, we review the cases performed as same-day arthroplasty surgeries compared to the same period in the previous 12 months. Methods We conducted a retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
(32 reference statements)
2
10
0
Order By: Relevance
“…They found that same day discharges were increased in those who underwent non-direct anterior approach THAs and TKAs in 2020 vs 2019. This was reported to be due to the desire to minimize risk of exposure to COVID-19 and to minimize inpatient bed use [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that same day discharges were increased in those who underwent non-direct anterior approach THAs and TKAs in 2020 vs 2019. This was reported to be due to the desire to minimize risk of exposure to COVID-19 and to minimize inpatient bed use [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the ongoing global COVID-19 pandemic, the importance of how to manage elective orthopedic surgery patients safely and effectively remains critical. Interestingly, some studies have shown that average LOS increased despite no difference in age or ASA post-COVID [30], whereas others have shown significant increases in same-day discharges without increases in postoperative readmissions or ED visits [31]. In the setting of limited healthcare resources and hospital beds, short-stay and outpatient arthroplasty are valuable programs in which to invest.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2020, the coronavirus disease of 2019 (COVID-19) pandemic has also increased the incidence of outpatient TKA, as inpatient beds and capacities were reserved for COVID-19 sufferers. The impact of the pandemic reinforced trends already in place due to value-based and bundled payment initiatives, and constant pressures on hospital costs [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%